Irrigation Water Management Technologies for Furrow‐Irrigated Corn that Decrease Water Use and Improve Yield and On‐Farm Profitability. Issue 1 (23rd May 2019) - Spencer, G. D.; Krutz, L. J.; Falconer, L. L.; Henry, W. B.; Henry, C. G.; Larson, E. J.; Pringle, H. C.; Bryant, C. J.; Atwill, R. L.
Abstract : Core Ideas: Irrigation water management practices decreased total water applied by 39.5%. Irrigation water management practices increased corn grain yield by 6.5 bu/acre. Irrigation water management practices increased irrigation water use efficiency by 51.3%. Withdrawal from the Mississippi River Valley alluvial aquifer by row‐crop irrigators in the Mid‐Southern USA has caused a precipitous decline in groundwater levels. The objective of this research was to determine if irrigation water management (IWM) practices can reduce the amount of water applied without having an adverse effect on corn ( Zea mays L.) grain yield and profitability when compared with the regional standard, that is, no IWM. The effect of computerized hole selection, surge irrigation, and irrigation scheduling based on soil moisture sensors on corn grain yield, total water applied, irrigation water use efficiency, and net returns above irrigation costs were determined from 2013 through 2017 on 18 paired fields with the same cultivar, soil texture, planting date, and management practices. One field was randomly assigned as the control (CONV) and was irrigated according to each producer's standard procedure while the other field used the IWM practices. Flowmeters were installed at the inlets to both fields and monitored the total volume of water applied while the cooperating farmers provided yield data. Relative to CONV, IWM decreased total water applied by 39.5% ( P = 0.002) while increasing corn grain yield by 6.5 bu/acre ( P = 0.0137), irrigation water use efficiency by 51.3% ( P = 0.0062), and net returns above irrigation costs from $25.03 to $39.18/acre for pumping depths ranging from 18 to 400 ft and diesel costs ranging from $1.60/gal to $3.70/gal ( P = 0.0115). Our research indicates that integrating computerized hole selection, surge flow irrigation, and irrigation scheduling with soil moisture sensors reduces the demand on depleted groundwater resources while improving corn grain yield, irrigation water use efficiency, and net returns above irrigation costs.